In vitro suppression of an amber mutation by a chemically aminoacylated transfer RNA prepared by runoff transcription. - Noren, C J (1990)
An amber suppressor tRNA was prepared in vitro by runoff transcription with T7 RNA polymerase. Both full-length tRNA and truncated tRNA lacking the 3' terminal pCpA from the acceptor stem could be synthesized from the same DNA template. Truncated runoff suppressor tRNA could be enzymatically ligated to phenylalanyl-pCpA to generate aminoacylated full-length suppressor tRNA (Phe-tRNA(CUA)). Phe-tRNA(CUA) is capable of suppressing an amber (UAG) mutation in vitro with equivalent efficiency as suppressor prepared by anticodon-loop replacement of a naturally-isolated tRNA. The ease of suppressor tRNA preparation using this method, compared to anticodon-loop replacement, greatly facilitates the use of chemically acylated suppressor tRNA's for site-specifically incorporating unnatural amino acids into proteins.